Discarded old antibiotics as a new arsenal for multi-resistant isolates in diabetic foot ulcer infections: therapeutic value of parenteral colistin versus multi-resistant Pseudomonas species isolate strains: case report - Shabhay, Ahmed; Chilonga, Jaffu O.; Mshana, Stephen E.; Shabhay, Zarina; Baal, Jeff Van; Salewi, Anande; Mwakyembe, Theresia; Muro, Florida; Chilonga, Kondo; Msuya, David; Chugulu, Samwel; Horumpende, Pius (International Journal of Basic & Clinical Pharmacology, 2021)
Antimicrobial resistance to current novel antibiotics is posing a major threat to both human and zoonotic life. In the absence of new novel antibiotics molecules, clinicians have resorted into a desperate last resort to review and re-introduce prior discarded antibiotics as their new weaponry in the fight against multi-resistant gram negative bacteria. We reported a case of a 77 year old bed ridden diabetic and hypertensive with renal impairment diagnosed with bilateral lower limbs wet gangrene. She underwent transfemoral on her right and transtibial amputation on her left lower limb. She developed surgical site infection on her right stump and wet gangrene on her left stump. Pus swab on her right stump revealed carbapenem resistant strains of Pseudomonas aeruginosa. She was instituted on parenteral colistin and showed no bacterial growth 7 days post treatment. She suffered an ischaemic cerebral vaso-occlusive stroke during her hospital stay. CT angiography of lower lung fields showed a large filling defect in the right main pulmonary artery extending to the lower lobe branches suggestive of right-sided pulmonary embolism. Our patient succumbed from her co-morbidities. Despite our patient succumbing to her multiple co-morbidities we reported this case to highlight the isolation of carbapenem resistant strains of P. aeruginosa and the efficacy and safety of colistin as a salvage antibiotic in renal impaired patients. Colistin can be safely used as a last reserve antibiotic for multi-resistant strains of P. aeruginosa infection even in patients with renal impairment.